(untitled) (Research, Society and Development, 2020)
The objective of this work was to prepare a hydrosoluble base extract of baru nut and to evaluate the physical and chemical stability, as well as the content of bioactive compounds. Three formulations with different proportions of baru:mineral water were prepared: 1:6, 1:8 and 1:10. Baru almonds were purchased from the local market in Rio Verde, GO, Brazil. The extracts were prepared with water, centrifuged, pasteurized, packaged and refrigerated at 5ºC. The pH, titratable acidity, colour parameters, antioxidant activity and total phenolic content of all formulations. Satisfactory levels of the bioactive compounds were found in all the proposed formulations of water soluble extract of baru. The 1:6 formulation presented minor changes throughout the ten days of storage. The processing used in this study was useful for obtaining the water soluble extract of baru.